ANALISIS TINGKAT PENGANGGURAN TERBUKA (TPT) PROVINSI JAWA TENGAH TAHUN 2016–2025 - Nafissa Ulfiyah; Dwi Desvita Sari; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
The Open Unemployment Rate (OUR) is an important indicator in measuring regional labor market conditions. This study aims to analyze the development of the Open Unemployment Rate in Central Java Province during the period 2016–2025 and to identify the factors influencing its changes. The research uses a descriptive quantitative approach with trend analysis based on secondary data. The results indicate that the unemployment rate in Central Java was relatively stable from 2016 to 2019, increased significantly in 2020 due to the COVID-19 pandemic, and gradually declined from 2021 to 2025. This decline reflects economic recovery and the improvement of labor absorption in various sectors. The study concludes that economic stability, government policies, and industrial development play significant roles in reducing unemployment at the regional level.